Community-based study of reproductive tract infections among women of the reproductive age group in the urban health training centre area in Hubli, Karnataka - Sangeetha S Balamurugan; N D Bendigeri (Wolters Kluwer Medknow Publications, 2012)
Background: Reproductive tract infections (RTIs) is a global health problem including both sexually transmitted infections (STIs) and non-sexually transmitted infections (non-STIs) of the reproductive tract. RTI/STI is an important concern, as it possess risk for human immunodeficiency virus transmission. Hence a community study was done in Hubli, in terms of active search of the cases based on the symptoms, clinical examination, and feasible laboratory tests along with providing treatment, counseling, and follow-up. Objectives: The objective was to know the prevalence of RTIs among the reproductive age group women and the socio-demographic factors influencing the occurrence of the disease. Materials and Methods: A cross-sectional study was done using a simple random sampling technique to select households. A pretested structured pro forma was used to collect data on RTIs from 656 women of 15-45 years, residing in the field practice area. This was followed by clinical examination and collection of samples for laboratory tests in Urban Health Training Centre, attached to Karnataka Institute of Medical Sciences, Hubli. Results: The prevalence of RTIs among the reproductive age group women was 40.4% based on their symptoms, with majority having abnormal vaginal discharge. The prevalence of RTIs based on clinical finding was 37.4% with majority having vaginitis. The laboratory test revealed a prevalence of 34.3% with majority having Candidiasis. The influence of socio-demographic factors like increased parity, poor socio-economic conditions, poor menstrual hygiene, illiteracy has its direct effect on occurrence of RTI in the community. Conclusion: This depicts that whereever possible, clinical and laboratory findings should support self-reported morbidity to know the exact prevalence of any disease in the community.